Peningkatan Daya Saing Produk Tani: Packaging dan Pembuatan Katalog di Kalurahan Tamanmartani, Yogyakarta - Victoria Sundari Handoko; Desideria Cempaka Wijaya Murti; Emerita Setyowati; Sesilia Eka Tri Astuti; Stephany Emmanuela Lesar; Gabriel Hacarya Adhi; Fridolin Satriya Indratma (Jurnal Atma Inovasia, 2026)
This community service activity aims to address the issue of low competitiveness in agricultural products by providing packaging and product photo catalogs to the farmer business group in Tamanmartani Village, Kalasan, Sleman. The problem faced by the farmer business group is related to the need for better product packaging and photo catalogs. The herbal agricultural products produced by this farmer business group have great economic potential; however, promotion is still limited, thus hampering wider marketing. The purpose of this community service activity is to increase the competitiveness of superior village agricultural products by improving packaging design and creating a photo catalog of ten agricultural products. The method applied is community development by providing support to the farmers’ business community through training and mentoring. The results of the activity showed improvement in the quality of visual identity, packaging, and product appearance, making the products more professional and marketable. The product photo catalog serves as a documentation and promotional tool to support digital marketing and strengthen the sustainable village economy.